Analysis of Business Environment and Medical Insurance Coverage Rates in the Destination of China's Migrant Population: Based on Geographically and Temporally Weighted Regression Model for Panel Data. (19th November 2022) - Liu, Yang; Chen, Xiaoyu; Zhang, Yujie
Abstract : Health risk is an important issue in the process of population spatial mobility, and it is also an important issue in the process of urbanization in China. Using the dynamic monitoring data of China's migrant population and 31 provincial business environment data from 2011 to 2018, this study systematically investigated the spatial distribution and evolution characteristics of the migrant population's participation in medical insurance in the destination areas and combined it with the Geographically and Temporally Weighted Regression Model for Panel Data (PGTWR) to analyze the impact of the regional business environment on the medical insurance coverage rate of the inflow area. The results are as follows: first, the spatial pattern of the insurance coverage rate is high in Eastern China and low in Western China. The areas with high insurance coverage rates are mainly distributed in the three major economic circles of China and provinces such as Shandong and Xinjiang. Second, there is significant spatial autocorrelation in the coverage rate, which shows that cities with high participation rates tend to form agglomeration areas in geographical space, and so do cities with low participation rates. The coverage rate of the popular areas is scattered, while the unpopular areas are concentrated. Third, the estimation results of the Geographically and Temporally Weighted Regression Model for Panel Data show that the macroeconomic and infrastructure indicators in the business environment have a greater impact on the insurance rate, while the impact of policy environment indicators is relatively weak. However, the overall improvement of the business environment can significantly improve the probability of the migrant population participating in medical insurance in the inflow area.